A New Species of Ismarus Haliday (Hymenoptera: Ismaridae) from Brazil and a New Occurrence Record for Ismarus gracilis Masner - Comério, Emerson Fraga; Perioto, Nelson Wanderley; Lara, Rogéria Inês Rosa (EntomoBrasilis, 2016)
A new species of Ismarus Haliday (Hymenoptera: Ismaridae) from Brazil is described, illustrated and a key to females of Ismarus of the New World is given. The geographic range of Ismarus gracilis Masner, 1976, is extended about 5,200 km farther to southeast. Uma Nova Espécie de Ismarus Haliday para o Brasil e novo Registro de Ocorrência de Ismarus gracilis Masner Resumo. Uma nova espécie de Ismarus Haliday (Hymenoptera: Ismaridae) do Brasil é descrita, ilustrada e é fornecida chave de identificação para fêmeas de Ismarus do Novo Mundo. A distribuição geográfica de Ismarus gracilis Masner, 1976 é estendida por cerca de 5.200 km em direção ao sudeste.